2012
DOI: 10.1155/2012/710486
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Profile of Newly Diagnosed Hypertensive Patients in Nnewi, South-East Nigeria

Abstract: Abnormalities in serum lipid and lipoprotein levels are recognized major modifiable cardiovascular disease and essential hypertension risk factors. The objective of this study was to examine the serum lipid patterns of newly diagnosed hypertensive patients attending a tertiary healthcare centre in South East Nigeria. Methods. Two hundred and fifty newly diagnosed adult hypertensive patients and an equal number of age- and sex-matched controls without hypertension were consecutively recruited from the Medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
9
34
4
Order By: Relevance
“…The view has been documented by Akintunde et al, though it appeared twice as often in their controls as in ours 11. Osuji et al also found a very high prevalence of low HDL-C in their participants, but a disproportionately higher prevalence in their controls 12. Our findings, however, differ from those in Caucasians, where reduced HDL-C is said to be uncommon in the ATP III 5.…”
Section: Discussionsupporting
confidence: 62%
“…The view has been documented by Akintunde et al, though it appeared twice as often in their controls as in ours 11. Osuji et al also found a very high prevalence of low HDL-C in their participants, but a disproportionately higher prevalence in their controls 12. Our findings, however, differ from those in Caucasians, where reduced HDL-C is said to be uncommon in the ATP III 5.…”
Section: Discussionsupporting
confidence: 62%
“…Significantly higher levels of blood sugar have been reported among hypertensive patients compared with normotensive controls. 33 Salmasi AM et al, reported a high prevalence of glucose abnormalities in hypertensive patients attending a hospital hypertension clinic. 34 There is therefore need for regular screening of hypertensive patients for glucose abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and dyslipidemia are cardiovascular risk factors that commonly coexist [1,2]. This coexistence increases the risk for cardiovascular morbidity and mortality [3].…”
Section: Introductionmentioning
confidence: 99%